2009
DOI: 10.1186/1471-2334-9-22
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of pertussis in Germany: past and present

Abstract: BackgroundCurrent and past pertussis epidemiology in the two parts of Germany is compared in the context of different histories of vaccination recommendations and coverage to better understand patterns of disease transmission.MethodsAvailable regional pertussis surveillance and vaccination coverage data, supplemented by a literature search for published surveys as well as official national hospital and mortality statistics, were analyzed in the context of respective vaccination recommendations from 1964 onward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
2
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 37 publications
4
59
2
9
Order By: Relevance
“…However, the incidence of pertussis has increased in recent years, both in Catalonia and other countries. [10][11][12][13] The rate of hospitalized cases < 1 y was 39 per 100,000 persons/y, compared with the 196 per 100,000 persons/y found by Somerville et al 14 or the 56 per 100,000 persons/y found by Elliot et al 15 In our study, 38.7% of hospitalized cases were correctly vaccinated, compared with the 66% found in an Australian study, 15 although another Australian study in New South Wales found that only 3% of hospitalized cases were correctly vaccinated, 16 and a German study found a rate of 4.5%. 17 A higher percentage of unvaccinated cases than vaccinated cases may be expected to be found in hospitalized cases, as vaccination should prevent both infection and the severity of cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of pertussis has increased in recent years, both in Catalonia and other countries. [10][11][12][13] The rate of hospitalized cases < 1 y was 39 per 100,000 persons/y, compared with the 196 per 100,000 persons/y found by Somerville et al 14 or the 56 per 100,000 persons/y found by Elliot et al 15 In our study, 38.7% of hospitalized cases were correctly vaccinated, compared with the 66% found in an Australian study, 15 although another Australian study in New South Wales found that only 3% of hospitalized cases were correctly vaccinated, 16 and a German study found a rate of 4.5%. 17 A higher percentage of unvaccinated cases than vaccinated cases may be expected to be found in hospitalized cases, as vaccination should prevent both infection and the severity of cases.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with other studies performed in the last decade. [11][12][13][14][15][16][17] Changes in the pertussis vaccination schedule in Catalonia occurred during the study period, similar to those occurring in other countries, such as Sweden, Italy and Finland. [18][19][20][21] These changes and changes introduced in the pertussis surveillance system in Catalonia make it difficult to interpret the data.…”
Section: Discussionmentioning
confidence: 99%
“…88 An epidemiological study carried out in Germany before re-unification showed similar results; the lack of booster dose at school age was clearly associated with a high incidence in the >5-y-age-group. 89 In the light of these data, it is clear that a booster dose at pre-school or school age should be included in pertussis vaccination schedules and that efforts should be made to achieve vaccine coverage in this age group.…”
Section: Strategies For the Prevention Of Pertussismentioning
confidence: 99%